Investigation of 1D Siliver Nanoparticle Arrays for Use as Molecule Concentration-Specific SERS Substrates. (26th November 2013) - Gao, Jun; Qian, Huan; Xu, Shang; Han, Min
Abstract : One-dimensional arrays of silver nanoparticles with a particle size of 10.5 nm and interparticle spacing of 8.5 nm were fabricated by depositing nanoparticles in gas phase on block copolymer self-assembled templates. The substrate showed a surface-enhanced Raman scattering (SERS) enhancement factor as high as 1 × 10 7 with good reproducibility and stability. The dependence of the average enhancement factor and the SERS intensity on the packing density of the analyte molecules were investigated. For a tiny amount of analytes in the range of 1 × 10 - 14 to 3 × 10 - 13 mol/mm 2, the SERS signal showed a linear dependence on the molecule packing density on a logarithmic scale, with a slope of about 1.25. The substrates are promising for quantitative detection of trace level molecules.